MODEL PEMBELAJARAN BRAIN BASED LEARNING UNTUK ANAK USIA DINI - Nia Kurniasari (QURROTI, 2019)
Early childhood (0-6 years) is in the golden age stage and experiences very rapid brain development. Early childhood education is useful as a forum that can develop all aspects of child development. In early childhood learning, learning strategies are needed that can increase the potential of children's intelligence. The brain is a very important organ for humans that functions as a nerve center, controlling all actions, thinking, processing information, analyzing and storing memories. Children's brain development reaches 80% at the age of 0-8 years, so it is called the golden ages. Therefore, the provision of educational stimuli, skills, moral and religious guidance is very appropriate to be given at this age. Brain-based learning, based on the Triune theory (activates the 3 parts of the brain), optimizes children's cognitive, affective and psychomotor abilities and empowerment. In addition, with learning designs and a conducive environment, children can learn easily in a fun way without coercion or pressure from outsiders. Brain Based Learning is oriented towards the potential of the child's brain so that learning leads to active learning. Based on the principles of Brain Based Learning, learning can be applied in PAUD using constructivist learning models, quantum teaching, multiple intelligence, problem-based learning and cooperative learning.